Development of failure detection system based on vibration signal for smart artificial heart: In vitro study - Tsujimura, Shinichi; Kuwabara, Takashi; Koguchi, Harutoshi; Yamane, Takashi; Tsutsui, Tatsuo; Sankai, Yoshiyuki (2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2008)
To realize safe and effective medical treatment for patients with implantable artificial hearts, we have developed a smart artificial heart (SAH). The SAH can grasp the mechanical condition of the artificial heart and the physiological condition of the patient. The purpose of this study is to develop a failure detection system based on the vibration signal from artificial heart in order to enhance the ability of failure detection for the SAH. We suppose this vibration signal reflects not only the mechanical condition of the artificial heart but also a part of the physiological condition of the patient. The developed failure detection system is composed of a vibration sensor unit and a failure detection algorithm. The algorithm has a standard frequency pattern, which is made from the vibration signal of good condition of both the artificial heart and patient. Observing the difference from the standard frequency pattern, the algorithm detects failure conditions. Therefore, this algorithm does not need prior knowledge of vibration characteristics corresponding to failures. After confirming that the vibration signal are affected by pump speed and pulsation in two kinds of mock circulatory loops, we performed thrombogenesis detection by using the failure detection system in mock circulatory loop with sheep blood. As a result, this system indicated a possibility of detecting the initial sign of thrombogenesis earlier than current signal. In conclusion, we think that this failure detection system can cooperate with other sensor systems of the SAH and enhance the ability of failure detection for the SAH.